The evolution of north-east Atlantic gadfly petrels using statistical phylogeography - Gangloff, B.; Zino, F.; Shirihai, H.; González-Solís, J.; Couloux, A.; Pasquet, E.; Bretagnolle, V. (Molecular ecology, 2013)
Macaronesia (north‐east Atlantic archipelagos) has been host to complex patterns of colonization and differentiation in many groups of organisms including seabirds such as gadfly petrels (genus Pterodroma). Considering the subspecies of widely distributed soft‐plumaged petrel for many years, the taxonomic status of the three gadfly petrel taxa breeding in Macaronesia is not yet settled, some authors advocating the presence of three, two or one species. These birds have already been the subject of genetic studies with only one mtDNA gene and relatively modest sample sizes. In this study, using a total of five genes (two mitochondrial genes and three nuclear introns), we investigated the population and phylogeographical histories of petrel populations breeding on Madeira and Cape Verde archipelagos. Despite confirming complete lineage sorting with mtDNA, analyses with nucDNA failed to reveal any population structuring and Isolation with Migration analysis revealed the absence of gene flow during the differentiation process of these populations. It appears that the three populations diverged in the late Pleistocene in the last 150 000 years, that is 10 times more recently than previous estimates based solely on one mtDNA gene. Finally, our results suggest that the Madeira petrel population is ancestral rather than that from Cape Verde. This study strongly advocates the use of nuclear loci in addition to mtDNA in demographical and phylogeographical history studies.